Wnt Signaling and Its Contribution to Craniofacial Tissue Homeostasis. (November 2015) - Yin, X.; Li, J.; Salmon, B.; Huang, L.; Lim, W.H.; Liu, B.; Hunter, D.J.; Ransom, R.C.; Singh, G.; Gillette, M.; Zou, S.; Helms, J.A.
A new field of dental medicine seeks to exploit nature's solution for repairing damaged tissues, through the process of regeneration. Most adult mammalian tissues have limited regenerative capacities, but in lower vertebrates, the molecular machinery for regeneration is an elemental part of their genetic makeup. Accumulating data suggest that the molecular pathways responsible for the regenerative capacity of teleosts, amphibians, and reptiles have fallen into disuse in mammals but that they can be "jumpstarted" by the selective activation of key molecules. The Wnt family of secreted proteins constitutes one such critical pathway: Wnt proteins rank among the most potent and ubiquitous stem cell self-renewing factors, with tremendous potential for promoting human tissue regeneration. Wnt reporter and lineage-tracing strains of mice have been employed to create molecular maps of Wnt responsiveness in the craniofacial tissues, and these patterns of Wnt signaling colocalize with stem/progenitor populations in the rodent incisor apex, the dental pulp, the alveolar bone, the periodontal ligament, the cementum, and oral mucosa. The importance of Wnt signaling in both the maintenance and healing of these craniofacial tissues is summarized, and the therapeutic potential of Wnt-based strategies to accelerate healing through activation of endogenous stem cells is highlighted.